SISTEM PENDUKUNG KEPUTUSAN PENILAIAN TENAGA KEPENDIDIKAN DENGAN METODE FUZZY ANALYTIC HIERARCHY PROCESS - Senas Salsabila (LPPM STMIK AMIK BANDUNG, 2022)
Employees are the main resource that is required to be able to provide the best service and optimal performance. The best employees can be judged from their good performance, which is one of the important aspects of a business entity, organization, or institution. A large number of data on employees or education personnel working in large educational institutions such as Jenderal Achmad Yani University (Unjani) is quite difficult to determine and identify educational personnel with good performance objectively because, without an objective assessment, the performance of education personnel can only be assessed by means of a subjective point of view. This can affect the lack of good and optimal performance of educational staff, so in overcoming this problem, this study build a web-based decision support system to select and assess alternative education personnel working at Unjani, including attributes or criteria, used consisting of criteria dynamic or can be added and/or changed as needed. The decision-making method used is the Fuzzy Analytic Hierarchy Process (F-AHP) method. The results of this study are the realization of a Decision Support System for Educational Personnel Assessment with the F-AHP method with an accuracy test result of 7.0%, which is expected to make it easier to assess the performance of exemplary educational personnel at Unjani and reduce the subjective element in the assessment, where the accuracy value comes from The assessment on an ongoing system where there is an assessment is subjective, while the Education Personnel Assessment Decision Support System has become objective, it's just that it has not been divided for each workgroup. Make alternative result data not separated from one group to another.